Complete mitochondrial DNA sequencing of Vieja synspila, a cichlid fish. (2nd January 2016) - Xu, Bin; Gao, Jianzhong; Wang, Xuelong; Chen, Zaizhong; Wang, Chenghui
Abstract: The Redhead cichlid ( Vieja synspila ) is an important aquarium fish and a useful phylogenetic organism of the Cichlidae family. In this study, we sequenced the mitochondrial genome of the Redhead cichlid for the first time. The mitogenome (16, 543 bp) had the typical mitochondrial characteristics of other cichlid fish, including 13 protein-coding, 22 tRNA, two rRNA genes and one putative control region. This sequence will be helpful in studying the phylogenetic relationships between cichlid fish.